2021
DOI: 10.1177/1748006x211020305
|View full text |Cite
|
Sign up to set email alerts
|

A combined approach of convolutional neural networks and machine learning for visual fault classification in photovoltaic modules

Abstract: Fault diagnosis plays a significant role in enhancing the useful lifetime, power output, and reliability of photovoltaic modules (PVM). Visual faults such as burn marks, delamination, discoloration, glass breakage, and snail trails make detection of faults difficult under harsh environmental conditions. Various researchers have made several attempts to identify visual faults in a PVM. However, much of the previous studies were centered on the identification and analysis of limited number of faults. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The faults detected in this case are mostly related to visible problems, such as delamination, burn marks and glass breakages. An important issue that makes the comparison between studies difficult is the difference between the data resolution used as input for each one of them, as images vary from PV cells [140] to aerial images [141]. [151] k-means, SVM and CNN MCC: 1.0 Detection of damaged modules on rooftops [141] Naïve Bayes, SVM, k-nearest neighbors, decision tree, RF and pretrained DL models Ac: 100% Detection of burn marks, delamination, discoloration, glass breakages and snail trails [152] DL Ac: 93% Masks of bird droppings Tables 6 and 7 present a summary of the methods for detecting and classifying faults in aIRT images of PV systems, using DIP and DL algorithms, respectively.…”
Section: Detection and Classification Of Faultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The faults detected in this case are mostly related to visible problems, such as delamination, burn marks and glass breakages. An important issue that makes the comparison between studies difficult is the difference between the data resolution used as input for each one of them, as images vary from PV cells [140] to aerial images [141]. [151] k-means, SVM and CNN MCC: 1.0 Detection of damaged modules on rooftops [141] Naïve Bayes, SVM, k-nearest neighbors, decision tree, RF and pretrained DL models Ac: 100% Detection of burn marks, delamination, discoloration, glass breakages and snail trails [152] DL Ac: 93% Masks of bird droppings Tables 6 and 7 present a summary of the methods for detecting and classifying faults in aIRT images of PV systems, using DIP and DL algorithms, respectively.…”
Section: Detection and Classification Of Faultsmentioning
confidence: 99%
“…An important issue that makes the comparison between studies difficult is the difference between the data resolution used as input for each one of them, as images vary from PV cells [140] to aerial images [141]. [151] k-means, SVM and CNN MCC: 1.0 Detection of damaged modules on rooftops [141] Naïve Bayes, SVM, k-nearest neighbors, decision tree, RF and pretrained DL models Ac: 100% Detection of burn marks, delamination, discoloration, glass breakages and snail trails [152] DL Ac: 93% Masks of bird droppings Tables 6 and 7 present a summary of the methods for detecting and classifying faults in aIRT images of PV systems, using DIP and DL algorithms, respectively. In general, the algorithms with the highest results are the ones dedicated to the detection of faults or the classification of a few types of faults, with the classification of many classes of faults being a much more complex task.…”
Section: Detection and Classification Of Faultsmentioning
confidence: 99%
“…In studies [ 106 , 107 , 108 , 109 ], researchers localized and identified different failures of a solar plant system based on CNNs that process the solar panels’ images, including thermographic images [ 106 , 107 , 108 ]. In Table 10 , we summarize the ML technologies for PV diagnostics from studies [ 106 , 107 , 108 , 109 , 110 , 111 , 112 ].…”
Section: Machine Learning Applications For a Solar Plant Systemmentioning
confidence: 99%
“…Reports reveal that renewable energy sources contribute about 27.3% of the total electricity production across the globe with PV-based power production accounting for about 2.8%. PV-based power production is placed next to wind energy power generation as one of the leading contributors to power generation [ 3 ]. PV-based power generation employs PV modules to convert the incident light into electricity.…”
Section: Introductionmentioning
confidence: 99%